The Reform of secondary education and the formation of the working class in the context of the crisis of capital (Research, Society and Development, 2019)
This article has the proposal to analyze the reform of secondary education and its developments in the formation of the working class in the context of the crisis of the capital of the 21st century. The article has a qualitative and bibliographical approach based on the classic works of Marxism such as Karl Marx and Friedrich Engels that discuss the theme of the situation and formation of the working class in capitalism. Due to the increasing precariousness of work, analyzes that seek to problematize the causes and consequences of such transformations in the world of work are essential to promote constructive debates for society. We discuss here also to evaluate the economic and political objectives of the Reform of High School, Theorize the Reformation of high school with as a parameter the Marxist theory, more specifically the theory of class struggle and analyze Law 13,415 of February 16, 2017 and its split in Law No. 9,394 / 96 LDB.